High-temperature and room-temperature compression deformation behavior comparing of GH4169 Alloy. Issue 1 (February 2021) - Zhang, Y W; Lu, X D; Su, X; Wen, B; Du, J H
Abstract: The hot deformation characteristics of a Ni-Fe based superalloy (GH4169) were studied in the temperature range 900-1020 °C and strain rate range 0.001-0.1 s −1 using hot compression tests. The cold deformation characteristics of the alloy were studied at room-temperature and strain rates of 0.1-1.0 s −1 using room-temperature compression tests. A hot deformation equation is given to characterize the dependence of peak stress with temperature and strain rate. A cold deformation equation is given to characterize the dependence of peak stress. Comparing the results of the high-temperature and room-temperature deformations of the GH4169 alloy indicated that hot deformation is sensitive to both temperature and strain rate, while the cold deformation is sensitive to strain. At room-temperature deformation conditions, for true strain ≈0.2, the dynamic recrystallization nucleates and grains refine.